Homology Modeling and Structural Dynamics of the Glucose Oxidase - Farhan Azhwin Maulana; Laksmi Ambarsari; Setyanto Tri Wahyudi (Indonesian Journal of Chemistry, 2020)
Glucose oxidase from Aspergillus niger IPBCC.08.610 (GOD_IPBCC) is a locally sourced flavoenzyme from Indonesia that can potentially be developed in a variety of industrial processes. Although this enzyme has a high activity in catalyzing the redox reactions, the use of this enzyme was still limited to be applied as glucose biosensor. Using information from the amino acid sequences, a computational structure of GOD_IPBCC was therefore designed by homology modeling method using two homologous structures of GOD from protein data bank (1CF3 and 5NIT) as the templates. The quality of the resulting structures was evaluated geometrically for selection of the best model, and subsequently, 50 ns of MD simulations were carried out for the selected model as well as the corresponding template. Results obtained from the validation analysis showed that the 1CF3 template-built structure was selected as the best reliable model. The structural comparison exhibited that the best-modeled structure consisted of two functional domains and three catalytic residues similarly to the corresponding experimental structure. The overall dynamic behavior of the 50 ns of the structure was structurally stable and comparable with that of the positive control both from globally and locally observations. Implications of these stable nature within the best-modeled structure unfold the possibilities in search of notable residues and their roles to enhance enzyme thermostability.